The Role of the Ancestral Yellowstone Plume in the Tectonic Evolution of the Western United States - Murphy, J. Brendan (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
Plate reconstructions indicate that if the Yellowstone plume existed prior to 50 Ma, then it would have been overlain by oceanic lithosphere located to the west of the North American plate (NAP). In the context of models supporting long-lived easterly directed subduction of oceanic lithosphere beneath the NAP, the Yellowstone plume would have been progressively overridden by the NAP continental margin since that time, the effects of which should be apparent in the geological record. The role of this ‘ancestral’ Yellowstone plume and its related buoyant swell in influencing the Late Mesozoic–Cenozoic tectonic evolution of the southwestern United States is reviewed in the light of recent field, analytical and geophysical data, constraints provided by more refined paleogeographic constructions, and by insights derived from recent geodynamic modeling of the interaction of a plume and a subduction zone.   Geodynamic models suggesting that the ascent of plumes is either stalled or destroyed at subduction zones have focused attention on the role of gaps or tears in the subducted slab that permit the flow of plume material from the lower to the upper plate during subduction. These models imply that the ascent of plumes may be significantly deflected as plume material migrates from the lower to the upper plate, so that the connection between the hot spot track calculated from plate reconstructions and the manifestations of plume activity in the upper plate may be far more diffuse compared to the more precise relationships in the oceanic domain. Other geodynamic models support the hypothesis that subduction of oceanic plateau material beneath the NAP correlates with the generation of a flat slab, which has long been held to have been a defining characteristic of the Laramide orogeny in the western United States, the dominant Late Mesozoic–Early Cenozoic orogenic episode affecting the NAP.   Over the last 20 years, a growing body of evidence from a variety of approaches suggests that a plume existed between 70 and 50 Ma within the oceanic realm close to the NAP margin in a similar location and with similar vigour to the modern Yellowstone hot spot. If so, interaction of this plume with the margin would have been preceded by that of its buoyant swell and related oceanic plateau, a scenario which could have generated the flat slab subduction that characterizes the Laramide orogeny.   Unless this plume was destroyed by subduction, it would have gone into an incubation period when it was overridden by the North American margin. During this incubation period, plume material could have migrated into the upper plate via slab windows or tears or around the lateral margins of the slab, in a manner consistent with recent laboratory models. The resulting magmatic activity may be located at considerable distance from the calculated hot spot track.   The current distribution of plumes and their buoyant swells suggests that their interaction with subduction zones should be common in the geological record. If so, the Late Mesozoic–Cenozoic evolution of western North America may represent a relatively modern analogue for such processes.